Enhanced Max-Min Algorithm For Resource Allocation In Cloud Computing - Pandaba Pradhan, Prafulla Ku. Behera , B N B Ray (International Journal of Advanced Science and Technology, 2020)
Cloud Computing is one of the leading technique which gathers together different computing techniques into one accomplishing a common objective .Cloud computing is an on-demand service because it offers dynamic flexible resource allocation for reliable and guaranteed services in pay as-you-use manner. The goal of cloud computing is to provide different services to multiple users simultaneously and efficiently. To achieve this goal adroitly, many cloud service providers face challenges to facilitate all the required resources to the users according to their demand. So the fundamental problems with cloud computing are resource allocation and resource scheduling. When scheduling resources in cloud environment, different tasks need to be executed simultaneously by the available resources in order to meet consumers’ expectations and to minimize completion time. To achieve this, we proposed a new noble mechanism known as Enhanced Max-Min (EMM) algorithm. The proposed scheduling algorithm increases efficiency in terms of reducing completion time as well as average waiting time by optimizing resource allocations in the cloud. The Max-Min algorithm gives priority to tasks with maximum execution time first before assigning those with the minimum execution time. So the EMM algorithm is used to improve the delay in executing tasks with minimum execution time. CloudSim is used to compare the effectiveness of the EMM algorithm with the traditional Max-Min algorithm. The experimented results show that our Enhanced Max-Min (EMM) algorithm is efficient.